ESTIMATION OF CURCUMINOIDS IN CURCUMA KARNATAKENSIS (WHITE TURMERIC) - AN ENDEMIC TAXON - Dh, Tejavathi; Bs, Sujatha; R, Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: To estimate the contents of curcuminoids in two samples of Curcuma karnatakensis collected from different localities. Methods: Quantification of curcuminoids was estimated by ultra-high performance liquid chromatography-mass spectrometry/selected reaction monitoring (UHPLC-MS/SRM) method in two samples of C. karnatakensis for the first time. Fine powder of rhizomatous rootstocks of two plant samples collected from different habitats were served as Samples A and B. The MS used for the metabolite analysis is a Vantage TSQ triple stage quadrupole MS equipped with heated electrospray ionization. The MS is coupled with an Agilent 1290 infinity UHPLC system. A stock solution of curcuminoid standard was prepared by dissolving 5 mg of standard in 1 mL of methanol. Seven different concentrations of standard (0.15-10 ng on column) were injected for the UHPLC-MS/SRM analysis. Separations were performed using a C-18 column with a flow rate of 0.2 mL/minute. Results: Contents of curcumin, demethoxycurcumin, and bisdemethoxycurcumin were found to be varied in two samples and lowest than any other species of Curcuma studied. Variation in the contents may be due to their different habitats in which they are growing. Conclusion: The present attempt of analyzing the contents of curcuminoids in this endemic taxon for the first time will provide the basis for further pharmacological analysis to authenticate the efficacy of these active principles as the curcuminoids are known for varied pharmacological activities.